The Effectiveness of Board Game Method on Reading Mastery - Juwita Boneka Sinaga (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This research aims to find the effectiveness of Board Game to Improve Students’ Reading Mastery for eleventh grade at SMK Widya Batam in Academic Year 2017/2018. To know the method is effective or not, the writer used true-experiment applied in XI.3 and XI.5. And to know how effective used Board Game to improve students’ Reading. Board Game made students interested to learn and enjoy the subject at school and their daily activity. The students will practice their knowledge by the game, especially with Board Game. And the teacher had the new method to teach the students with game. The instrument is Task Based Picture, and analyzed the data by t-test. The result showed that there was significant to students taught by Board Game. The writer takes the conclusion that the method is effective for teaching process. The method was okay because it was own good and effective for learners.